Genetic variation in the lymphotoxin-α (LTA)/tumour necrosis factor-α (TNFα) locus as a risk factor for idiopathic achalasia. Issue 9 (20th November 2013) - Wouters, Mira M; Lambrechts, Diether; Becker, Jessica; Cleynen, Isabelle; Tack, Jan; Vigo, Ana G; Ruiz de León, Antonio; Urcelay, Elena; Pérez de la Serna, Julio; Rohof, Wout; Annese, Vito; Latiano, Anna; et al.
Abstract : Background: Idiopathic achalasia is a rare motor disorder of the oesophagus characterised by neuronal loss at the lower oesophageal sphincter. Achalasia is generally accepted as a multifactorial disorder with various genetic and environmental factors being risk-associated. Since genetic factors predisposing to achalasia have been poorly documented, we assessed whether single nucleotide polymorphisms (SNPs) in genes mediating immune response and neuronal function contribute to achalasia susceptibility. Methods: 391 SNPs covering 190 immune and 67 neuronal genes were genotyped in an exploratory cohort from Central Europe (589 achalasia patients, 794 healthy volunteers (HVs)). 24 SNPs (p<0.05) were validated in an Italian (160 achalasia patients, 278 HVs) and Spanish cohort (281 achalasia patients, 296 HVs). 16 SNPs in linkage disequilibrium (LD) with rs1799724 (r 2 >0.2) were genotyped in the exploratory cohort. Genotype distributions of patients (1030) and HVs (1368) were compared using Cochran–Armitage trend test. Results: The rs1799724 SNP located between the lymphotoxin-α ( LTA ) and tumour necrosis factor-α ( TNFα ) genes was significantly associated with achalasia and withstood correction for testing multiple SNPs (p=1.17E-4, OR=1.41 (1.18 to 1.67)). SNPs in high LD with rs1799724 were associated with achalasia. Three SNPs located in myosin-5B, adrenergic receptor-β-2 and interleukin-13 ( IL13 ) showed nominally significant association to achalasia that was strengthened by replication. Conclusions: Our study provides evidence for rs1799724 at the LTA/TNFα locus as a susceptibility factor for idiopathic achalasia. Additional studies are needed to dissect which genetic variants in the LTA / TNFα locus are disease-causing and confirm other variants as potential susceptibility factors for achalasia.